Redes de Bragg em fibra óptica para medição de parâmetros relacionados as máquina elétricas - Sousa, Kleiton de Morais (2016)
This paper presents the application of fiber Bragg gratings (FBG) for parameters measurement in electrical machines. The results allow to explore new instrumentation techniques and show the potential for industrial applications, presenting the measurement in an hydroelectric power plant, and laboratory research, such as the dynamic stator strain measurement. Each instrumentation technics presented in this paper has a potential to use isolated or integrated in order to obtain a multiparameter instrumentation in hydroelectric power plants or industrial environments that using induction motors in its production process. This paper is organized in a collection of articles, and the FBG applications are the temperature measurement and simulation of a rectifier bridge used to adjust the rotor field current of a power generator, a magnetic field sensor, , a biaxial optical accelerometer and the measurement of the stator dynamic strain of an induction motor. The results for the thyristor temperature measurement show the dependence of temperature and excitation current, where current oscillations lead to temperature fluctuations. The simulation of the thermal model presents a 1.5oC error compared to measures by the FBGs. The field sensor is based on magnetostriction, property where the magnetic material undergo deformation in the presence of a magnetic field. For this sensor are used two FBGs for temperature measurement and deformation in Terfenol-D, material with magnetostrictive properties. In the magnetic field sensor the response is a function of temperature, where the magnetostriction and saturation presents non-linear behavior varies as a function of temperature. Stator strain measurement using the FBGs has a good relationship signal noise, 80 dB for the fundamental harmonic and the observed frequencies in the vibration are theoretically expected. Moreover, with the use of two sensors can be determine the rotating nature of the air gap magnetic force. Finally, the biaxial optical accelerometer does not have is insensitive to temperature variations and can be applied for measuring vibration in electrical machines.